Compact neutron generators for the calibration of low background experiments. (November 2019) - Chepurnov, AS; Gromov, MB; Ionidi, V Yu; Kaplii, A A; Kirsanov, MA; Klenin, A A; Kolesnikov, D A; Kubankin, A S; Maslenkina, A Yu; Oleinik, A N; Selivanova, D A; Shchagin, A V
Abstract: In the coming years, the compact monoenergetic neutron generators (CNG) producing up to 10 4 n/s may become an alternative to the standard neutron sources based on radioactive isotopes for the calibrations of neutrino and dark matter detectors. Such neutron generators have a typical size of about several centimetres, they may be manufactured using low-background materials and may require only low voltage power supply for operation. We discuss the advantages and disadvantages of two main types of the compact neutron generators, namely a pyroelectric neutron source and a high voltage neutron generator. Also the results of the technical analysis of the possibilities to apply such sources for the calibration of low-background experiments are given, the variant of the internal device design is shown and the full-size compact neutron generator prototype are presented.